ECOMUSICOLOGY, INDIGENOUS KNOWLEDGE AND ENVIRONMENTAL DEGRADATION IN IBADAN, NIGERIA - Titus, Olusegun Stephen (International Library of African Music, 2019)
Research on Yoruba popular music has tended to draw attention to its interest in romance and the accumulation of wealth. Inadequate attention has been paid to its engagement with the environment. Ibadan, the capital of Oyo State in Nigeria has witnessed perennial flood disasters, and this has been a concern of Yoruba musicians. This article is an ethnographic investigation of the place of music in the flood disasters of Ibadan as addressed in the songs of Yoruba musicians, Kollinton Ayinla, Foyeke Ajangila, Ebenezer Obey and Agbada Owo. The article describes the connections between the cultural past, when indigenous knowledge was respected and flooding was avoided, and the present, when it was forgotten, and flooding became a constant. Based on the very specific, local context of Ibadan, I argue that calls for the return of indigenous knowledge as propagated in popular music could be a way forward in environmental crises currently experienced around the globe.
Keywords: Environmental degradation; Popular music; Ecomusicology; Natural disasters; Ibadan; Flood; Nigeria; African Music